Storage sites in seeds of Caesalpinia echinata and C. ferrea (Leguminosae) with considerations on nutrients flow - Teixeira, Simone de Pádua; Machado, Sílvia Rodrigues [UNESP] (Brazilian Archives of Biology and Technology, 2008)
As sementes de Caesalpinia echinata e C. ferrea comportam-se como endospérmicas, apesar de descritas na literatura como exendospérmicas e endospérmicas, respectivamente. Desta forma, o objetivo deste trabalho foi comparar, em termos ultra-estrutural e histoquímico, a natureza das substâncias de reserva e seus tecidos acumuladores, bem como o fluxo de nutrientes nas sementes destas espécies. Os cotilédones em C. echinata acumulam carboidratos, lipídios e proteínas, mobilizados da periferia para o centro, como visto pelo posicionamento dos plasmodesmas. O endosperma em C. ferrea acumula carboidratos e lipídios, e em C. echinata, acumula substâncias nos estádios iniciais da embriogênese. Este tecido desenvolve um haustório calazal agressivo, que transporta substâncias para o endosperma propriamente dito e deste para o embrião, fato confirmado pela presença de células de transferência no endosperma.

The seeds of Caesalpinia echinata and C. ferrea behaved as typical endospermic seeds, despite their different morphological classification (exendospermic seeds were described for C. echinata and endospermic seeds for C. ferrea). Then, the aim of this work was to compare, under ultrastructural and histochemical terms, the nature of the storage substances and their accumulation sites, as well as the nutrient flow in seeds of these species. Cotyledons in C. echinata accumulate carbohydrates, lipids and proteins, which are mobilized from the outer to the inner parts as revealed by the position of plasmodesmata. Endosperm in C. ferrea accumulates carbohydrates and in C. echinata accumulates substances during the initial embryogenic phases. Such tissue develops a chalazal haustorium that is responsible for the transport of substances into the endosperm itself and from it into the embryo, confirmed by the presence of transference cells.
Keywords: Cotyledon; embryo; endosperm; histochemistry; reserve substances; ultrastructure